2018
DOI: 10.3390/ijms19092815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Cold Stress on Liver O-GlcNAcylation and Glycometabolism in Mice

Abstract: Protein O-linked β-N-acetylglucosamine glycosylation (O-GlcNAcylation) regulates many biological processes. Studies have shown that O-GlcNAc modification levels can increase during acute stress and suggested that this may contribute to the survival of the cell. This study investigated the possible effects of O-GlcNAcylation that regulate glucose metabolism, apoptosis, and autophagy in the liver after acute cold stress. Male C57BL/6 mice were exposed to cold conditions (4 °C) for 0, 2, 4, and 6 h, then their li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 76 publications
(86 reference statements)
0
27
0
Order By: Relevance
“…The modification of proteins with O‐GlcNAc is thus limited by UDP‐GlcNAc availability and occurs in a specific manner on serine or threonine residues of nearly 4000 proteins, thus modulating protein‐protein interactions, phosphorylation and enzymatic stability . In this manner, protein modification by O‐GlcNAc controls a wide range of processes including signaling networks, transcription, cell metabolism, amino acid and nucleotide metabolism, nutrient sensing and the cell stress response . Within this broad control of cell physiology, it is emerging that O‐GlcNAc modification also controls specific aspects of endocytic membrane traffic, including that of proteins that regulate membrane transport of metabolites, ions and proteins, although much remains to be understood about this phenomenon.…”
Section: Direct Control Of Endocytic Membrane Traffic By Metabolitesmentioning
confidence: 99%
“…The modification of proteins with O‐GlcNAc is thus limited by UDP‐GlcNAc availability and occurs in a specific manner on serine or threonine residues of nearly 4000 proteins, thus modulating protein‐protein interactions, phosphorylation and enzymatic stability . In this manner, protein modification by O‐GlcNAc controls a wide range of processes including signaling networks, transcription, cell metabolism, amino acid and nucleotide metabolism, nutrient sensing and the cell stress response . Within this broad control of cell physiology, it is emerging that O‐GlcNAc modification also controls specific aspects of endocytic membrane traffic, including that of proteins that regulate membrane transport of metabolites, ions and proteins, although much remains to be understood about this phenomenon.…”
Section: Direct Control Of Endocytic Membrane Traffic By Metabolitesmentioning
confidence: 99%
“…The posttranslational attachment of β-N-glucosamine (GlcNAc) to serine/threonine residues of proteins (O-GlcNAcylation) is the product of the hexosamine biosynthetic pathway (HBP), which integrates glucose, amino acid, fatty acid, and nucleotide metabolism to generate the donor substrate uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) (Hart and Akimoto 2009;Yang and Qian 2017). O-GlcNAc signaling is highly sensitive to various forms of cellular stress, including heat/cold shock (Kazemi et al 2010;Yao et al 2018), hypoxia (Liu et al 2014), and neuronal excitotoxicity (Zhu et al 2015). Although the O-GlcNAc axis is only beginning to be described in neuronal alterations, many upstream kinases important for memory consolidation are known to intersect with signaling to OGT and O-GlcNAcylation, including CamKII (Erickson et al 2013), PKA (Xie et al 2016), PKC (including PKC-zeta [Miura et al 2018]), CREB (Rexach et al 2012;Xie et al 2016), and many others (Hart et al 2011).…”
mentioning
confidence: 99%
“…Another study showed that maintaining energy balance during acute cold exposure (−15°C, 4 h) results in an increase in blood glucose concentration (stimulation of glycogenolysis and gluconeogenesis) and activation of the protein kinase B (Akt) pathway, which promotes the production and increase of ATP concentration in rat liver cells ( Wang et al, 2013 ). A sharp increase in ATP concentration was also found in the liver of male C57BL/6 mice after 6 h of cold exposure (4°C) ( Yao et al, 2018 ). Therefore, existing evidence indicates that, in response to cold stress, many cells increase their energy resources.…”
Section: Discussionmentioning
confidence: 94%